Ethnobotany of the Mountain Regions of Brazil - Book Review - Tungga Dewi, Imelda Zahra; Indah Sari, Anggi Mei; Solo, Intan Riani (Ethnobotany Research and Applications, 2025)
Ethnobotany of the Mountain Regions of Brazil, edited by Reinaldo Farias Paiva de Lucena and Denise Dias da Cruz. 2023. Springer Nature Switzerland AG, 2023, pp 796, €2799.99 (Hardcover), €299.59 (eBook), ISBN 9783030872502 (Hardcover), 9783030872519 (eBook). As highlighted in Ethnobotany of the Mountain Regions of Brazil, edited by Reinaldo Farias Paiva de Lucena and Denise Dias da Cruz, which is part of the Ethnobotany of Mountain Regions series published by Springer, this book presents an in-depth study of ethnobotany in Brazil's semi-arid regions, particularly within the Caatinga ecosystem. With 105 plant species covered, this book explores the close relationship between traditional communities and local biodiversity. It primarily focuses on the utilization of plants for various purposes, such as medicine, food, and construction, while also highlighting the role of traditional knowledge in conservation and sustainable development. Although the Caatinga is not a typical mountain region, the book explores formations such as the região serrana (500–1000+ m) unique ecosystems like brejos de altitude integrate species from both the Caatinga and the Atlantic Forest.